Legal Protection of Human Rights and Local Communities: Impact of Tourism Business - Indra Ratna Sari; Andin Rusmini (Saniya Institute, 2023)
This research aims to describe the government's protection of the human rights of local communities in the tourism sector as stated in tourism law number 10 of 2009 concerning tourism. The method used in this journal is descriptive analysis, based on literature studies. This journal concludes that protecting the rights of local communities in the tourism business sector is something that needs attention. It has been stated in the statutory regulations implemented by the government itself regarding the obligations of companies to carry out their business in Indonesia. The inclusion of these regulations should be able to limit corporate efforts in practicing their business so that there are no violations of human rights. Apart from that, the relevant government also plays an important role in preventing things that could harm local communities.